Resource productivity in 7 steps: How to develop eco-innovative products and services and improve their material footprint - Michael Lettenmeier; Holger Rohn; Christa Liedtke; Friedrich Schmidt-Bleek; Katrin Bienge; Dafne Mazo Urbaneja; Jade Buddenberg (Wuppertal Institut für Klima, Umwelt, Energie, 2009)
This compendium Resource Productivity in 7 Steps is intended to give practical advice to designers, engineers, distributors, banks, lawmakers and others how to increase the resource productivity of goods and services (dematerialisation). The eco-innovative (re-)design of products begins with the definition/description of the benefit or service, which a product provides to its user. The use of MIPS (Material Input Per unit Service) helps to develop solutions that can provide this benefit with the least possible quantity of natural resources, from. It measures the material and energy input of a product throughout its life-cycle, from cradle to cradle (production of raw materials, manufacturing, transportation, use, disposal). Thus, material and energy consumption can be minimised while satisfying the demand and decoupling of the economic activities from resource use. The brochure describes in seven steps how to gain more resource productivity. It provides several worksheets for the innovation process and material intensity factors for the calculation of the material footprint. A translation into traditional chinese is also available. – – Die Broschüre Resource Productivity in 7 Steps (Ressourcenproduktivität in sieben Schritten) soll Designern, Ingenieuren, Vertriebsunternehmen, Banken, Gesetzgebern und anderen praktische Hinweise geben, wie man die Ressourcenproduktivität von Gütern und Dienstleistung steigern, also ihre Dematerialisierung vorantreiben kann. Die öko-innovative (Neu-)Gestaltung von Produkten beginnt mit der Definition des Nutzens bzw. der Dienstleistungen, die das Produkt den Nutzern erbringt. Die Verwendung von MIPS (Material Input Per unit Service oder output) hilft dabei, Lösungen zu entwickeln, die den geringst möglichen Einsatz natürlicher Ressourcen benötigen. Gemessen werden Material- und Energieverbrauch eines Produkts über seinen gesamten Lebenszyklus (Gewinnung und Aufbereitung der Rohstoffe, Herstellung, Vertrieb, Nutzung und Entsorgung), also von der Wiege bis zur Wiege. Auf diese Weise können Energie- und Ressourcenverbrauch gesenkt und dennoch die Nachfrage befriedigt werden. Somit wird die Entkopplung von wirtschaftlicher Tätigkeit und Ressourcenverbrauch möglich. Die in englischer Sprache verfasste Broschüre zeigt die praktischen Schritte zur Steigerung der Ressourcenproduktivität. Sie stellt Arbeitsblätter für den Innovationsprozess und Materialintensitätsfaktoren für die Berechnung des Material Footprint zur Verfügung. Eine Übersetzung in traditionellem Chinesisch liegt ebenfalls vor.
urn:nbn:de:101:1-2010050774
Keywords: 330